Study of effect of propranolol, atenolol and celiprolol on exercise induced changes in heart rate, blood pressure and peak expiratory flow rate in healthy human volunteers - Patel, Sumit P.; Shah, Rima B. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Beta blockers are known to cause attenuation of sympathetic stimulation mediated increase in cardiovascular parameters. Very few studies are available in Indian set-up comparing these changes between different beta blockers available in market. The objective of the study was to compare efficacy and safety of propranolol, atenolol and celiprolol on heart rare, blood pressure and airway resistance, both at rest and during exercise. Methods: A prospective interventional study was carried out involving 72 healthy volunteers in the clinical pharmacology laboratory. Participants were divided in three groups of 24 each and given single oral doses of propranolol 40 mg, Atenolol 50 mg and celiprolol 40 mg was given to the participants. Exercise given in the form of step ladder test and hand grip dynamometer and effect on the different parameters like HR, SBP, DBP and PEFR were recorded before and immediately after exercise and compared. Results: All the three drugs were effective in attenuating the exercise induced cardiovascular parameters (p <0.05). Drug A cause change in HR, SBP, DBP and PEFR significantly (p <0.05). Change in SBP was more significant with drug B while significant difference was found in HR, SBP and DBP before and after exercise in drug C in both SL and HGD tests. No significant difference was found between the drug groups (p >0.05). No adverse effects were reported in the study participants. Conclusions: All the three drugs are effective in attenuating cardiovascular changes after sympathetic stimulation like exercise and there was no significant difference among them.